A repository of 14 PCR-loci Italian gene frequencies in the World Wide Web. - Maviglia, R; Dobosz, M; Boschi, I; Caglià, A; Hall, D; Capelli, C; d'Aloja, E; Pescarmona, M; Moscetti, A; Pascali, V; Destro-Bisol, G (2001)
A collection of 6830 typing results produced by the Immunohematology Laboratory at the UCSC, pertaining to 11 STRs (FES/FPS, vWA31, HUMTH01, F13A1, MBP, D21S11, D7S460, D18S51, CD4, TPOX, CSF1PO) and 3 AmpFLPs (D1S80, APO-B, COL2A1), is publicly available as an electronic archive at a website.